2009
DOI: 10.4049/jimmunol.0804344
|View full text |Cite
|
Sign up to set email alerts
|

TLR-Induced Local Metabolism of Vitamin D3 Plays an Important Role in the Diversification of Adaptive Immune Responses

Abstract: The addition of monophosphoryl lipid A, a minimally toxic derivative of LPS, to nonmucosally administered vaccines induced both systemic and mucosal immune responses to coadministered Ags. This was dependent on an up-regulated expression of 1α-hydroxylase (CYP27B1, 1αOHase), the enzyme that converts 25-hydroxycholecalciferol, a circulating inactive metabolite of vitamin D3, into 1,25(OH)2D3 (calcitriol). In response to locally produced calcitriol, myeloid dendritic cells (DCs) migrated from cutaneous vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 41 publications
1
57
0
1
Order By: Relevance
“…In other studies, incorporation of 1,25(OH) 2 D 3 (100 ng) into a subcutaneous vaccine consisting of diphtheria and alum promoted the migration of cutaneous DC to secondary lymphoid sites such as the Peyer's patches. 15 This study details new investigations into the ability of topical 1,25(OH) 2 …”
Section: Discussionmentioning
confidence: 99%
“…In other studies, incorporation of 1,25(OH) 2 D 3 (100 ng) into a subcutaneous vaccine consisting of diphtheria and alum promoted the migration of cutaneous DC to secondary lymphoid sites such as the Peyer's patches. 15 This study details new investigations into the ability of topical 1,25(OH) 2 …”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported the expression and metabolic activity of Cyp27b1 in human moDC that subsequently influences T‐cell activity, although the degree to which DC can produce 1,25‐OH‐VD3 in vitro varies with their activation and differentiation status 23, 67, 68, 69. Similarly to macrophages, direct stimulation of human and mouse GM‐CSF‐DC with pathogen‐associated molecular pattern or pro‐inflammatory cytokines triggers Cyp27b1 expression, as does T‐cell contact, especially in a pro‐inflammatory cytokine milieu 23, 69, 70, 71. Moreover, DC isolated from skin‐draining afferent lymph of sheep have also been shown to metabolize VD3 to 1,25‐OH‐VD3 67.…”
Section: As a Source Of 125‐oh‐vd3 For T Cell Programmingmentioning
confidence: 99%
“…Vitamin D is essential for bone health [1][2][3][4] and optimal cardiovascular [5][6][7][8][9][10] and innate immune [11][12][13][14][15] function. Levels of 25-hydroxy vitamin D (25(OH)D) are most often used to assess adequacy of vitamin D stores.…”
mentioning
confidence: 99%